Mechanism of Ultrasonic Guided Wave Excitation and Sensing in Pressure Vessel Structures Under Boundary Condition Effects - Napoleon Kuebutornye; Zipping Wang; Jiazhen Zhang; Dongwei Shang; Qingwei Xia (e-Journal of Nondestructive Testing)
This study proposes a finite element-based multiphysics simulation of ultrasonic guided wave (GW) propagation under pressure conditions in a pressure vessel structure (15 kg LPG cylinder) utilizing boundary conditions. The two key mechanisms influencing GW propagation are stress-induced changes in material properties (acoustoelastic effect), which causes phase shifts, and geometric deformation (thickness and curvature variations), which impacts GW amplitude. The simulation is carried out using COMSOL Multiphysics, where the solid mechanics module models the boundary loads and pressure effects, while electrostatics simulates the behavior of piezoelectric transducers as both wave excitation and receiving elements as the boundary conditions. A non-linear numerical model capturing the relationship between pressure loads and GW characteristics such as phase velocity and attenuation is developed. Simulation results under pressure loading conditions are compared with experimental data, showing good agreement in phase and amplitude variations, thereby validating the proposed model.